2014
DOI: 10.1093/ntr/ntu168
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Impact of Point-of-Sale Tobacco Promotion on Smoking

Abstract: The existing evidence supports a positive association between exposure to POS tobacco promotion and smoking. This review provides evidence to support the continuation of POS tobacco display bans in those jurisdictions where such legislation has been introduced and strengthens the evidence encouraging similar policies in jurisdictions without a POS display ban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 47 publications
4
151
0
2
Order By: Relevance
“…Of these, 13 were judged to have met the inclusion criteria and were reviewed in full. These included 5 of the 10 studies on children and youth included by Paynter and Edwards,10 6 of the 9 studies included by Robertson et al ,9 and an additional 2 studies subsequent to the search dates in the reviews (see online supplementary table S1). Eleven articles reported associations for behavioural outcomes (table 1), and six for cognitive outcomes (table 2); four studies reported both behavioural and cognitive outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 13 were judged to have met the inclusion criteria and were reviewed in full. These included 5 of the 10 studies on children and youth included by Paynter and Edwards,10 6 of the 9 studies included by Robertson et al ,9 and an additional 2 studies subsequent to the search dates in the reviews (see online supplementary table S1). Eleven articles reported associations for behavioural outcomes (table 1), and six for cognitive outcomes (table 2); four studies reported both behavioural and cognitive outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Literature searches were similar to those used previously9 10 and were conducted in June 2014 using MEDLINE (OvidSP), Scopus and Web of Science. An initial search for the keywords ‘tobacco’ OR ‘smoking’ OR ‘cigarette*’ was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamura et al 2014;Paynter and Edwards 2009;Robertson,et al 2016;Robertson et al 2015). Restrictions on tobacco product displays at the point-of-sale are currently implement- restrictions has been associated with a reduction in the frequency of consumers' tobacco purchases in Australia and Canada by up to 30% (Carter, Phan, and Mills 2014;Li et al 2013).…”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%
“…14,15 Tobacco retailers provide ubiquitous cues to smoke. [16][17][18][19] Proximity to tobacco retailers is associated with decreased success in tobacco use cessation, 20,21 although this may be true only in lower socioeconomic status neighborhoods. 22 Tobacco retailer density has been associated with smoking behaviors [23][24][25] and with youth initiation; 26 however, some findings are mixed.…”
Section: Original Investigationmentioning
confidence: 99%